STARTUP INCUBATION AND ACCELERATORS IN AFRICA; ARE START-UPS SCALING UP IN KENYA? - Muathe, Stephen; Otieno, Victor (American International Journal of Social Science Research, 2022)
Incubators and accelerators help businesses overcome obstacles such as lack of space, cash, mentoring, and training. While business incubation is not a new idea worldwide, its function in developing and scaling up start-ups remains vacant in Kenya. This study examined whether start-up incubators and accelerators help Kenyan companies grow. This study focused on the importance of accelerators and incubators in Kenya. Kenya is recognized as the second most important innovation cluster in Sub-Saharan Africa. Despite the tremendous influence of incubators and accelerators on the growth of start-ups in Kenya, their long-term sustainability suffers partly due to a weak knowledge-building environment, inadequate marketing research, poor customer service, a lack of adequate personnel training, and inefficient demand forecasting and analysis, all of which is the Covid-19 outbreak has hampered start-up growth, lowering their formation, survival, and progress. Finally, incubators help entrepreneurs succeed by providing them with space, guidance, mentorship, connections to investors, and internet access. To safeguard established start-ups from the Covid-19 outbreak and guarantee them focus on scaling up, the problem may be overcome by assisting new and existing start-ups. Policymakers can alleviate short-term worries by encouraging short-term liquidity and capital, as well as fostering new business prospects. Policies that encourage new businesses and promote entrepreneurial potential may help speed up the recovery and sustain aggregate employment. Advocate for the Kenyan government to alter existing national legislation and enhance coordination among the numerous players in the start-up ecosystem. JEL Classification Codes: M13, N8.